The New Middle Classes Globalizing Lifestyles, Consumerism and Environmental Concern - Lange, Hellmuth; Meier, Lars (Springer Netherlands : Imprint: Springer, 2009)
The new middle classes of developing countries are held responsible for boosting extremely resource-intensive lifestyles beyond the OECD-world thus thwarting ongoing efforts to attain a more sustainable future. But how homogeneous are their consumption patterns and why should not globalization include the extension of environmental concern, too? "The New Middle Classes" challenges a narrow understanding of lifestyles and consumption by analyzing the issue not only in terms of attitudes and preferences but of socio-economic features and governmental policies, too. Original contributions from internationally renowned researchers bring fresh multidisciplinary insights in both theoretical and empirical respect. "The New Middle Classes" will be of interest mainly to sociologists, political scientists, human geographers, and anthropologists.